An Analysis Of Deixis In The Song ‘To The Bone’ By Pamungkas - Fahad Abdulloh; Budik Kusworo (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study analyzes deixis in Pamungkas's song "To The Bone" using Levinson's (1983) framework to examine how deictic elements create emotional resonance. A qualitative analysis of the lyrics identified 92 deictic expressions: personal (83), spatial (8), and temporal (1). The predominance of personal deixis (90.2%), particularly first-person ("I", "me") and second-person ("you") references, establishes an intimate singer-listener connection, enhancing the song's confessional tone. Minimal temporal ("now") and spatial ("that", "there") deixis suggests a focus on emotional immediacy rather than specific time/space. Findings reveal deixis functions as: (1) a tool for building intimacy, (2) a marker of authenticity, and (3) a means for listener identification. The study contributes to music pragmatics by demonstrating how deixis shapes meaning in popular music, offering insights for both linguistic analysis and songwriting.